Rancang Bangun Website Arsip Aktivitas Harian Pegawai Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia Kabupaten Badung - Andika Putra, Ida Bagus; Mastrika Giri, Gst. Ayu Vida (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 8 No 1 (2019): JELIKU Volume 8 No 1, Agustus 2019DO - 10.24843/JLK.2019.v08.i01.p07, 2019)
Information technology currently has a very important take on the development of human activities, for example, the application of information technology in the form of management information systems at the Human Resources Development and Empowerment Agency (BKPSDM) of Badung Regency. This information system helps employees in BKPSDM especially in the data field to help their work. But one of the problems that occurs in BKPSDM in the data field is that employees are still searching for employee map numbers still manually by asking the employee NIP and looking for employee map numbers by looking at the hardcopy that is already in the closet. So that the time needed to find the employee map number is long enough so that the time to do the other tasks is quite drained. From these problems the author makes a solution that is by making an information system that can find the employee map number by simply entering the NIP on the system named E-Staffing archive. This information system can also import personnel data with the .xlsx file format and export personnel data to file.xls format. This system is built using the CodeIgniter (CI) framework with a PHP backend and MySql database.